Learning strategies, academic performance, and knowledge areas: Analysis with university students (Revista Contexto & Educação, 2025)
The use of learning strategies (LS) is central in the self-regulation of learning, encompassing techniques, processes, or activities that students undertake to complete a task or achieve goals. This research analyzed the use of LS by university students and correlated it with academic performance, considering the areas of their courses. The sample consisted of 539 students from academic programs across the three fields of knowledge (Humanities, Exact Sciences, and Health) and all years of study. Data were collected through a sociodemographic questionnaire and an LS scale. The Academic Performance Coefficient was obtained as a measure of performance. Students reported using most LS. The most frequently used strategies were: rereading the material, reviewing answers before submitting the test, taking notes, selecting main ideas, and organizing necessary materials. No significant relationship was found between the factors of the LS Scale and academic performance. The scale items were analyzed separately and correlated, considering the area of knowledge. It is concluded that the relationship between LS and performance is complex and multifaceted, depending on various factors such as the area of knowledge and learning context. The discussion highlights the need to characterize the strategic student not only by the number of strategies used but also by the quality and conscious use of these strategies.
Keywords: Higher education; Learning strategies; Academic achievement